The health and economic burden of invasive pneumococcal diseases attributable to PCV21 versus PCV20 serotypes among adults aged ≥ 45 years in Spain - Muloongo Simuzingili; Silvia Fernández-Soberón; Zinan Yi; Nicole Cossrow; Kelly D. Johnson; Kwame Owusu-Edusei (BMC Public Health, 2026)
Abstract Background The 21-valent pneumococcal conjugate vaccine (PCV21) is a new vaccine that includes eight serotypes not found in any currently licensed vaccines. This study estimates the lifetime clinical and economic burden of invasive pneumococcal disease (IPD) in Spain attributable to PCV21 serotypes compared to PCV20 serotypes among Spanish adults aged ≥ 45 years. Methods Using a published state-transition Markov model, the lifetime IPD cases, deaths, and direct medical costs (in 2024 euros) associated with serotypes included in PCV21 and PCV20 were estimated among adults aged 45–64 and ≥ 65 years across three risk groups (low-risk, at-risk, and high-risk). A one-way sensitivity analysis was performed to identify key model inputs influencing the incremental costs of IPD. Results PCV21 serotypes were associated with approximately 17–20% more lifetime IPD cases and deaths than PCV20 serotypes among adults aged ≥ 45 years. The estimated lifetime direct medical cost for PCV21 serotypes (€291 million) was 14% higher than that of PCV20 (€255 million) among adults aged 45–64 years. Similarly, PCV21 serotypes (€193 million) were 20% higher than PCV20 serotypes (€161 million) among those aged ≥ 65 years. The eight unique serotypes targeted by PCV21 accounted for 29,501 cases and 6,059 deaths (approximately 18–19% of PCV21 serotypes), contributing over €97 million to direct lifetime IPD costs. The highest burden was consistently observed in high-risk groups. Conclusions The serotypes targeted by PCV21 impose a significantly higher health and economic burden of IPD in Spain relative to PCV20. Consequently, PCV21 may help reduce the health and economic burden of IPD among Spanish adults, supporting its incorporation into national vaccination guidelines and adult immunization strategies.